Educational research trends in information communication technology - Syed Hassan, Sharifah Sariah; Hashim, Che Noraini (IIUM Press, 2014)
The integration of information communication technology (ICT) in teaching and learning has paved a new wave to the area of Instructional Technology for teaching and learning. The discussion of this book centers on the issues and research of communication via technology that affects teaching and learning. Thus, communication online, ethics of teaching and learning, teaching strategies, evaluation program framework, communication management in distance education and cyber ethics are explored. The discussions are elaborated based on comparison and contrast from both Western and Islamic perspectives. This book is beneficial for Masters students who are taking the course EDT 6610 Issues and Research in Instructional Technology. The terms Information technology and Instructional technology have been used interchangeably in the educational research. Sharifah Sariah Syed Hassan and Che Noraini have written the first chapter. The chapter introduces the research trend discussing on communication trend using social networks from both Islamic and Western perspectives. In the subsequent chapter as discussed by Sharifah Sariah Syed Hassan and Nik Suryani, , a case study has also been elaborated to show relationships of teaching strategies, meta-cognitive skills and student centred learning when video project is incorporated. Based on the communication and integrating technology in teaching, the next chapter has been written by Hazlina. The writer explores the ethics of online teaching according to Islamic perspectives. In chapter four written by Enas Said, the discussion centers in the teaching strategies using Twitter as a communication tool for stimulating writing skills. In chapter five, Mwebasa Umar elaborates the evaluation framework of Instructional Technology programme. In chapter six, communication management in distance education is discussed and followed by the cyber ethics from Islamic perspectives. This chapter has been written by Bakare Kazeem Kayode. In the final chapter, Abdul Salam Abdul Hameed has discussed on cyber ethics from Islamic perspectives. All the referred verses of Quran and Hadith for all the chapters involved are quoted from www.quranexplorer.com and www.sahih-bukhari.com